Management of mesh complications following surgery for stress urinary incontinence or pelvic organ prolapse: a systematic review. (1st November 2019) - Carter, P; Fou, L; Whiter, F; Delgado Nunes, V; Hasler, E; Austin, C; Macbeth, F; Ward, K; Kearney, R
Abstract : Background: Mesh surgery for stress urinary incontinence or pelvic organ prolapse can result in complications such as mesh exposure, mesh extrusion, voiding dysfunction, dyspareunia, and pain. There is limited knowledge or guidance on the effective management for mesh‐related complications. Objective: To determine the best management of mesh complications; a systematic review was conducted as part of the national clinical guideline 'Urinary incontinence (update) and pelvic organ prolapse in women: management'. Search strategy: Search strategies were developed for each indication for referral. Selection criteria: Relevant interventions included complete or partial mesh removal, mesh division, and non‐surgical treatments such as vaginal estrogen. Data collection and analysis: Characteristics and outcome data were extracted, and as a result of the heterogeneous nature of the data a narrative synthesis was conducted. Main results: Twenty‐four studies were included; five provided comparative data and four studies stated the indication for referral. Reported outcomes (including pain, dyspareunia, satisfaction, quality of life, incontinence, mesh exposure, and recurrence) and the reported incidences of these varied widely. Conclusions: The current evidence base is limited in quantity and quality and does not permit firm recommendations to be made on the most effective management for mesh‐related complications. Robust data are needed so that mesh complications can be managed effectively in the future. Tweetable abstract: Systematic review demonstrates that the outcomes following mesh revision surgery are highly variable. Tweetable abstract: Systematic review demonstrates that the outcomes following mesh revision surgery are highly variable.